Cytotoxic activity of aeroplysinin-1 against colon cancer cells by promoting β-catenin degradation. (July 2016) - Park, Seoyoung; Kim, Joo-Hyun; Kim, Jung Eun; Song, Gyu-Yong; Zhou, Wei; Goh, Sung-Ho; Na, MinKyun; Oh, Sangtaek
Abstract: An aberrant accumulation of β-catenin in intestinal epithelial cells is relevant to the development and progression of colon cancer and is thus a potential target for the development of therapeutics for this malignancy. Here, we used cell-based natural compound screening with genetically engineered HEK293 reporter cells to identify aeroplysinin-1, a brominated tyrosine derivative originated from marine sponges, as an inhibitor of Wnt/β-catenin signaling. Aeroplysinin-1 suppressed the β-catenin response transcription that was activated by Wnt3a-conditioned medium or 6-bromoindirubin-3′-oxime (an inhibitor of glycogen synthase kinase-3β) by promoting the proteasomal degradation of intracellular β-catenin. Consistently, aeroplysinin-1 decreased the amount of intracellular β-catenin and repressed the expression of β-catenin/T-cell factor-dependent genes, thereby inhibiting the proliferation of colon cancer cells. In addition, apoptosis was elicited by aeroplysinin-1, as indicated by the increase in the population of Annexin V-FITC stained cells and caspase-3/7 activities in DLD-1 colon cancer cells. These findings indicate that aeroplysinin-1 exerts its antiproliferative activity by attenuating Wnt/β-catenin signaling and may have potential as a chemopreventive agent for human colon cancer. Highlights: Aeroplysinin-1 is a novel inhibitor of the Wnt/β-catenin pathway. Aeroplysinin-1 promotes β-catenin degradation. Aeroplysinin-1 inhibits the proliferation of DLD-1 colon cancer cells.